(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In this paper, we proposed a class of ratio estimators for finite population variance. The proposed estimators were obtained by transforming Javed et al. (2018) estimators. The mean square errors (MSEs) of the proposed estimators have been obtained up to first order of approximation using Taylor’s Series Expansion and the conditions for their efficiencies over some existing variance estimators have been established. The efficiencies of proposed estimators based on optimal value of the constant, exhibit significant improvement over the estimators considered in the study. The numerical illustration was also conducted to corroborate the theoretical results. The results of the empirical study show that the proposed estimators are more efficient over existing estimators.